PENGARUH PELAYANAN TERHADAP KEPUASAN PELANGGAN DI VILA AYANNA, DESA CANGGU-BALI - Mutria Farhaeni; Ni Ketut Widiyasari (STIE BIITM, 2020)
ABSTRACTThe purposed of this study to find out if services has influence to customer satisfaction at AyannaVilla, Canggu Village-Bali, and to find out how much service gives an influence to customersatisfaction at Ayanna Villa, Canggu Village-Bali. The population this research are the customerwho stayed at Ayanna Villa, Canggu Village-Bali. Samples were taken from 60 respondentsusing a random sample. Data collection done by spread the questionnaire. The analysistechnique used in this study was classical assumption test, simple linear regression analysis, ttest analysis and determination analysis. From the simple linear regression analysis test, theservice variable (X) has regression coefficient equal to 0,164 that have positive effect tocustomer satisfaction (Y) and value from t-count (3,170)> t-table (1,672) with significance level0,002 (<0.05). That’s meaning the service (X) has significant influence to customer satisfaction(Y) at Ayanna Villa, Canggu Village-Bali are acceptable. Based on determination test, theservice has an influence to customer satisfaction of 14.8% and the remaining 85.2% by othervariables not examined in this study.